The impact of empathy with nature on tourists’ responsible behavioral intentions in natural heritage tourism: the moderating roles of escapism and awe - Wang, Kang; Huang, Shuangjun; Chen, Zhen; Liu, Yidong (Frontiers in Psychology, 2026)
IntroductionNatural heritage tourism provides opportunities for visitors to engage with ecological and cultural resources, yet encouraging responsible tourist behavior remains a persistent challenge for sustainable destination management. This study examines how tourists’ perceptions of natural and cultural environments shape their intentions to behave responsibly, with a particular focus on the mediating role of empathy with nature and the moderating influences of perceived escapism and awe.MethodsUsing Shennongjia in Hubei Province, China, as the study site, data were collected through structured questionnaires administered to tourists. Structural equation modeling (SEM) was employed to analyze the relationships among environmental perceptions, empathy with nature, responsible behavioral intentions, and the effects of escapism and awe.ResultsFindings show that both natural and cultural environmental perceptions significantly enhance empathy with nature, which in turn positively predicts tourists’ economic and non-economic responsibility behaviors. Empathy with nature mediates the effects of both environmental perceptions on responsible behaviors. Perceived escapism moderates the relationship between natural environmental perceptions and empathy, whereas awe strengthens the association between empathy and non-economic responsibility behaviors. However, escapism does not significantly moderate the influence of cultural perceptions, nor does awe significantly moderate the link between empathy and economic responsibility behaviors.DiscussionThis study clarifies the dual roles of natural and cultural stimuli in shaping empathy-driven responsible behavior among tourists. The differentiated moderating effects of escapism and awe reveal nuanced boundary conditions for promoting responsible actions. Practically, the results highlight the importance for destination managers to integrate natural and cultural experiences, cultivate visitors’ empathy with nature, and strategically evoke escapism and awe to strengthen both economic and normative forms of sustainable tourist behavior.